Objective IELTS. Advanced : - Black, Michael (Cambridge University Press, 2006)
Objective IELTS is a 2-level IELTS preparation course providing comprehensive training for both the Academic and General Training modules. The course is uniquely informed by the Cambridge Learner Corpus, using analysis of real IELTS candidate papers. The 2 levels of Objective IELTS can be used on their own or consecutively, so that lower-level students requiring a high band score can start preparing early. Each level offers 60-80 hours of study, which can be extended using the Workbook and CD-ROM.